Breastfeeding, socioeconomic status, and long-term postpartum weight retention - Saralyn F. Foster; Christian Vazquez; Catherine Cubbin; Amy R. Nichols; Rachel R. Rickman; Elizabeth M. Widen (BMC, 2023)
Abstract Background Almost half of all pregnant women in the United States gain weight above Institute of Medicine gestational weight gain guidelines. Breastfeeding has been shown to reduce weight retention in the first year postpartum; however, women with lower socioeconomic status (SES) tend to initiate breastfeeding less often than women with higher SES. We investigated associations between duration of breastfeeding with mother's long-term postpartum weight status at 4-10 years and evaluated whether the associations varied by SES. Methods Maternal and infant dyads (N = 2144 dyads) are from the Geographic Research on Wellbeing survey (GROW), 2012-2013, a long-term, cross-sectional follow-up of the Maternal and Infant Health Assessment (MIHA) based in California, USA. Pre-pregnancy body mass index (BMI) was obtained from self-report of height and weight during MIHA, while breastfeeding history and self-report of current body weight was collected at the 4-10 year GROW postpartum visit. SES score was derived from a composite score of percent federal poverty level and education and was dichotomized into High and Low SES groups at a score of three. Multivariable linear regression was used to examine association between breastfeeding and maternal weight status, and to examine for effect modification by SES. Results Average long-term weight retention 4-10 years postpartum was 4.0 kg. Fewer lower SES vs. higher SES women breast fed at least six months (51% versus 70%, p < .001) or ever breastfed (74% versus 89%, P < .001). Women who breastfed at least six months had lower long-term postpartum weight retention compared to those who did not (b = -1.06 kg, (-1.93, 0.25); p = 0.01); however, these association did not vary by SES. Conclusion Six months of breastfeeding is associated with lower BMI at 4-10 years and lower body weight, and effects do not vary by SES. Future policies and guidelines should consider building an infrastructure that is supportive of longer breastfeeding duration. Moreover, further research is needed to identify the impact of additional behavioral and environmental factors on long-term maternal weight status. Understanding the drivers of excessive weight retention pospartum can help us not only improve the pregnant person's health but the health of their children.